Identifikasi Gangguan Jaringan Dengan Metode Certainty Factor Di PT.Telkom Malang Guna Peningkatan Pelayanan Customer - Prasetyo, Egar Abdi (LPPM STIKI MALANG, 2021)
Telkom Malang is a state-owned company engaged in information and communication technology services with a product called Internet Digital Home (INDIHOME). Installation activities to handling network problems are the responsibility of PT. Telkom to get good customer value. But the fact in the field of increasing number of disturbances makes technicians overwhelmed with work orders and results in a long queue for handling disturbances. Meanwhile, the handling of disturbances, especially logic incidents, can be carried out by customers with the help of developing information systems in the form of a decision support system. The decision support system for Indihome network disruption resolution using the Certainty Factor method is very helpful for customers to find solutions to handle Indihome network disturbances which have an impact on reducing disturbances and are profitable for PT Telkom. So that PT Telkom can monitor disturbances and become evaluation materials to improve the quality of its products, as well as to improve customer service.